IMPORTANCE OF FOOD SECURITY: ROHINGYA REFUGEE IN COX’S BAZAR CAMP - Ayoade Ahmad, Abdullahi; Zulaikha Ramlan, Ain; Ladiqi, Suyatno; Farhana Mohd Noor, Nursairah (International Journal of Psychosocial Rehabilitation, 2020)
Food is one of the basic essential needs for every living thing. Man as a special creature as every opportunity and right to access the food for its sustainability. However, due to certain arising issues such as natural disaster, internal conflict and even war, food security has been one of the issue affecting most of our nowadays societies. The conflict in Myanmar has shown us how Muslim ethnic Rohingyas are suffering from the oppressive treatment of other ethnic namely; Burmese supported by Myanmar’s government. This situation forces Rohingyas to run for their lives and seek refuge in another country as refugees. One of the refugee camps that homed the Rohingya refugees is known as Cox’s Bazar in Bangladesh. Due to their relocation, they have limited access especially to adequate shelter and food, a situation that affects their wellness. Despites they have left their country for safety, the cooperation and assistance from international community is needed to solve the issue of food security of Rohingya refugees. This paper discusses the challenges faced by Rohingya refugees on food security, the examination of food security level and what need to be done. It finally investigates on the role of international community in solving the issue of food security in the Cox’s Bazar camp. The research adopted analytical and descriptive methods, while secondary sources such as book, journals and other relevant materials are utilized. The research concluded with recommendations to the refugees, the host nation and the international community for a better life for Rohingya refugees.